2009
DOI: 10.1021/jp911081b
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Sensitivity of Circular Dichroism to Long-Range Excitonic Couplings in Helical Supramolecular Assemblies

Abstract: Circular dichroism (CD) spectroscopy is an ideal tool for studying the self-assembly of helical supramolecular assemblies since it is very sensitive to extended excitonic couplings between chiral chromophores. We show that the CD spectrum retains its high sensitivity to long-range interactions even in the presence of extreme disorder and strong interaction with vibrations when excitations are mainly localized on individual molecules. We derive a universal expression for the first moment of the CD spectrum of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 38 publications
3
46
0
Order By: Relevance
“…The strong cofacial stacking of PBIs in the aggregates of 1 also hampered the chiral arrangement of PBI units, thereby resulting in the weak CD and negligible CPL. Meanwhile, the helical assemblies formed from 2 exhibited high CPL activity owing to the effective summation of individual g lum values in the exciton‐coupled assembled system 15b. The long‐range excitonic coupling between the chromophoric units in the self‐assembled state would contribute to enhanced g lum values at the aggregate region of the spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…The strong cofacial stacking of PBIs in the aggregates of 1 also hampered the chiral arrangement of PBI units, thereby resulting in the weak CD and negligible CPL. Meanwhile, the helical assemblies formed from 2 exhibited high CPL activity owing to the effective summation of individual g lum values in the exciton‐coupled assembled system 15b. The long‐range excitonic coupling between the chromophoric units in the self‐assembled state would contribute to enhanced g lum values at the aggregate region of the spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Although the noncovalent interactions that link the individual molecules within the LH antennae are weak, the excitation transfer interactions between the molecules are relatively strong; new excited states, so-called Frenkel excitons (13), are generated that are delocalized over a number of molecules (1). These delocalized excitons are key to nature's efficiency and are therefore of high interest (14)(15)(16)(17)(18)(19)(20).To create such efficient LH systems, nature assembles molecular subunits into individual supramolecular structures, which are then further assembled into close-packed superstructures (1, 4, 7-10, 12, 21). This hierarchical assembly is a generic motif of nature's photosynthetic systems.…”
mentioning
confidence: 99%
“…Although the noncovalent interactions that link the individual molecules within the LH antennae are weak, the excitation transfer interactions between the molecules are relatively strong; new excited states, so-called Frenkel excitons (13), are generated that are delocalized over a number of molecules (1). These delocalized excitons are key to nature's efficiency and are therefore of high interest (14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…In calculations based on the semiempirical Holstein Hamiltonian, it has been demonstrated that the CD spectrum of π-stacked aggregates may show a slow convergence with respect to the number of molecules in a stack. 33 It was reported that up to a tenth nearest-neighbor couplings had a significant effect on the CD intensity. 33 In our results for the ethylene dimer, it was noted that, at the prototypical intermolecular separation distance of 3.5 Å, the separation of the dark and bright Frenkel exciton states was as large as 40 nm and the resulting CD spectrum did not take the expected excitonic lineshape seen for prototypical stacks.…”
Section: Ethylene Stacksmentioning
confidence: 99%
“…33 It was reported that up to a tenth nearest-neighbor couplings had a significant effect on the CD intensity. 33 In our results for the ethylene dimer, it was noted that, at the prototypical intermolecular separation distance of 3.5 Å, the separation of the dark and bright Frenkel exciton states was as large as 40 nm and the resulting CD spectrum did not take the expected excitonic lineshape seen for prototypical stacks. In other words, for a system such as ethylene, where the area of the π-system is very small, the CD spectrum of the aggregate appears not to be well decomposed into dimer contributions.…”
Section: Ethylene Stacksmentioning
confidence: 99%